LABIAL GINGIVAL RECESSIONS AND THE POST TREATMENT PROCLINATION OF MANDIBULAR INCISORS - Haider Zahid; Ahmad, Nofil; Faiza Ijaz (Journal of Ayub Medical College Abbottabad, 2024)
Background: Labial gingival recessions are a common periodontal condition characterized by the apical migration of the gingival margin, which can impact dental aesthetics and health. The proclination of mandibular incisors following orthodontic treatment has been implicated as a contributing factor to the development or exacerbation of such recessions. This study investigates the relationship between post-treatment incisor proclination and the occurrence of labial gingival recessions to inform clinical strategies for minimizing periodontal complications. Objectives were to evaluate the relationship between the mandibular incisor’s proclination and the emergence of gingival recession. Methods: After obtaining ethical committee approval, this prospective cohort study was conducted at the Department of Orthodontics, Frontier College of Dentistry from March 2019 to March 2024, involving 180 participants meeting the inclusion criteria and followed up after one year. Assessments included clinical crown height measurements, gingival recession presence, and cephalometric analysis. Crown heights were measured on plaster models at TS, T0, and T5 with an electronic caliper. Recessions were noted at T5 if the labial cement enamel junction was exposed. Cephalometric radiographs marked specific landmarks to assess incisor inclination at TS, T0, and T5. Participants were grouped based on post-treatment incisor inclination: <95°, 95°–100.5°, and >100.5°, with further analysis focusing on the non-proclined (<95°, N=60) and proclined (>100.5°, N=60) groups. Results: The mean age of all the patients were 36.99±10.7 years. The mean elevation in clinical crown heights from T0 to T5 for mandibular incisors showed a range of 0.79 to 0.87 mm in the non-proclined group and the proclined group, respectively, with no significant P-value. The mean increase in clinical crown heights for the lower incisors post-treatment (from T0 to T5) varied from 0.58 mm to 1.32 mm in the Proclined group and 0.64 mm to 0.89 mm in the non-proclined group Conclusion: It was concluded that the inclination of mandibular incisors did not pose an elevated risk for the occurrence of gingival recession during a five-year observation period when compared to non-proclined teeth.